Bone mineral density of tibae and femura of broiler breeders: growth, development and production - Almeida Paz,ICL (2006)
The aim of this study was to follow-up the physiological variations in the development of the bone tissue, associating them with the egg production curve. This study was carried out in the facilities of the Faculdade de Medicina Veterinária e Zootecnia of the UNESP, Botucatu, Brazil. Twenty-three families of Ross broiler breeders were used, each family consisting of 13 females and 1 male, distributed in 23 pens of 5.0m² each. The management was that recommended by the genetic company manual (Agroceres Ross, 2003), with daily feeding until 6th week of age; and birds were fed according to a 5:2 schedule (5 days fed, 2 days of fasting) between 7 and 17 weeks of age, returning to daily feeding starting at 18 weeks of age. Birds did not receive afternoon calcium supplementation. On the fourth week of rearing, 84 females were removed for bone analyses of the right tibia and femur, using optical densitometry in radiographic images technique. These analyses were sequentially carried out in 4, 8, 12, 15, 20, 24, 30, 35, 42, 47, and 52 week-old birds. The egg production curve of the birds was followed-up and associated to bone mineral density results. For bone mineral density evaluation (BMD) birds were divided by weight categories as light, intermediate, or heavy within each data age. BMD values of the tibias were not influenced by weight range, but by the age at collection. On the other hand, interactions were found among femur BMD values and weight and age categories. There was no correlation between eggshell quality and femur BMD. A negative correlation (-0.15) was observed between tibia BMD and eggshell percentage. It was possible to conclude that the egg production has little influence on bone mineral density of the birds probably because there was no need of bone mineral mobilization during the production period, since the observed egg production was below that observed under commercial conditions.